HOLOCENE ALLUVIAL DEPOSITS MEANING IN A SEMI-ARID ENVIRONMENT: A CASE STUDY ON SERTANEJA DEPRESSION (BAHIA STATE/BRAZIL) - Lima, Kleber Carvalho [UNESP] (2019)
Ephemeral drainage basins and their alluvial deposits may have characteristics that contribute to the understanding of Holocene time-scale climate dynamics. Although widely studied in semiarid contexts of different countries, their paleoclimatic significance is still poorly understood in Brazil. In this research, we analyzed the characteristics of alluvial deposits in two small drainage basins, located in the southern semi-arid, central-north sector of the Sertaneja Depression - State of Bahia/Brazil. Our purpose also included interpreting the Holocene climatic conditions that contributed to the processes of alluvial deposit formation. We performed the geomorphological mapping, allostratigraphic layers identification on field trip, Particle Size Distribution (PSD) analysis, sediment morphology analysis, and Optically Stimulated Luminescence (OSL) dating. Alluvial deposits showed characteristics associated with crystalline rocks and ephemeral streams such as [i] spatial discontinuity along the drainage channel; [ii] depositional architecture indicative of bedding lateral migration and laminar flows; [iii] predominance of gravel and coarse sand, poorly sorted and; [iv] statistical parameters that suggest past episodes flows. The depositional events occurred in the Middle Holocene - Upper Holocene transition, between 4.4 kyr - 3.5 kyr B.P. and between 1.1 kyr B.P. to the present. These deposits have relations with dry climatic conditions established in the last 4 kyr.